FAKTOR FAKTOR YANG MEMPENGARUHI KEJADIAN LOW BACK PAIN PADA PEKERJA LAUNDRY - Dahlan Gunawan; Andi Ipaljri Saputra; Aplan jumadi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Low Back Pain is a common health problem worldwide that often results in activity limitations and absenteeism from work. Methods: The method of this research is an observational analytical sample ninth in this study using nonprobability sampling method with accidental sampler technique with a sample number of 97 respondents. Data is the primary data of the questionnaire. Data analysis using univariate and bivariate analysis. with accidental sampling technique with a sample size of 97 respondents. Results: The results of the study showed several factors that cause Low Back Pain in laundry workers: age, body position, and repetition that causes low back pains. The p-value is obtained in a sequence of p = 0.795, p = 0.010, p = 0,001. Significant factors affecting the occurrence of Low Back Pain are body position and repetition, while age is not significant. Conclusion: Based on the Chi-Square correlation results, there is a significant relationship between body position and repetition with Low Back Pain incidents, whereas age has no significant relationship to low back pains in laundry workers. Keywords: Low Back Pain, Laundry worker